Synthesis, Characterization and Evaluation of the Antibiofouling Potential of Some Metal and Metal Oxide Nanoparticles - Lucía Blanco-Covián (Applied Sciences, 2020)
This study explores the potential antibiofouling capacity of coatings based on mixes of poly vinyl alcohol (PVA)-glutaraldehyde (GA) incorporating additions of metal and metal oxide nanoparticles (TiO2, ZnO, CuO, AgNPs and Ag-TiO2NPs). Such a kind of hybrid polymer-nanoparticle mix (PVA/GA/ nanoparticles (NPs)) was uniformly applied by spin coating on the surface of a laboratory raceway and tested in freshwater loaded with green algae communities. The results showed PVA/GA was a convenient carrier for the nanoparticles tested. Image analysis of the coatings showed that Ag-TiO2 nanoparticles exhibited a significant improvement of the antibiofouling effect when compared with that of AgNPs and TiO2-NPs. The effect of the Ag-TiO2 NPs loaded coating about four times better than that of ZnO-NPs. A consistent experimental methodology was developed to test the antibiofouling capacity of the coatings and the hybrid coatings developed have demonstrated promising results as environmentally friendly antibiofouling materials.